Graduates Profile of Undergraduate Law Schools in Peruvian Public Universities: A Qualitative Research - Hugo GONZÁLEZ (Communications of International Proceedings, 2022)
This paper analyzes the graduate profile of public university law schools in Peru licensed by Sunedu. A qualitative research has been conducted based on the analysis of documents published by the universities on their website, through the Atlas ti program to systematize the categories: administration of justice and legislation, consulting and advisory, ethics and values, communication skills, teaching, sustainability, teamwork, research, conflict or problem solving, critical thinking, leadership, litigation or sponsorship. Those most relevant are problem solving, research, ethics and values, communication skills; those that are developed to a lesser extent correspond to teaching, sustainability, and teamwork; therefore, they need to be made explicit and broadened by law schools. In addition, it is evident that no homogeneity or unity exists among the profiles analyzed.
Keywords: Graduate profile; problem solving; research; ethics.